Epidemiological analysis of self-medication of non-opioid analgesics in students of a higher education institution in western Paraná (Research, Society and Development, 2023)
Objective: To analyze the prevalence of self-medication of non-opioid analgesics among medical students at FAG University Center. Method: This is a cross-sectional, observational study. The study population consisted of medical students at the Centro Universitário FAG in the city of Cascavel, Paraná State, Brazil. A validated questionnaire with social and drug consumption variables was applied, followed by statistical analysis. The collected information was tabulated using a Microsoft Office Excel® spreadsheet. The study was approved by the Research Ethics Committee (CEP) by opinion 6.040.008. Results: There were 100 participants in this research. Among them, 86% stated that they had already purchased over-the-counter medications. In this study, the factor that influenced most of the interviewees to decide for self-medication was the indication by pharmacists, representing 47.9% of the answers. Among the options of medications contained in the questionnaire, the most used is Paracetamol, with 70% of the answers. It can be observed that the most common etiology of self-medication is headache. Added to this is the fact that most of the students affirmed that they felt more able to self-medicate because they were in a medical course. Conclusion: This study allowed us to visualize the epidemiological aspects, the prevalence, the main epidemiology and the drugs most used for self-medication among medical students.